1998
DOI: 10.1136/bmj.316.7146.1709
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of headache after lumbar puncture: questionnaire survey of neurologists and neurosurgeons in United Kingdom:

Abstract: The aetiology of headache after lumbar puncture is related to the hole left in the dura after the needle has been withdrawn, which allows the cerebrospinal fluid to leak out of the subarachnoid space. The headache can persist for prolonged periods and predispose to subdural haematomas, which are associated with a high mortality. Tourtellotte showed that this headache could be significantly reduced by using smaller needles.1 Also, among needles of the same size, those with atraumatic blunt tips are associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 4 publications
1
16
0
2
Order By: Relevance
“…Despite the overwhelming evidence in support of the use of smaller, non-cutting needles for diagnostic lumbar punctures, the use of larger cutting needles is still widespread in neurological departments [3,4,21]. In our outpatient clinic, where a cutting 22 G needle had previously been the needle of choice, we performed a prospective, interventional study, in order to test the feasibility, drawbacks, and potential benefits of changing the needle to a 25 G non-cutting needle.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Despite the overwhelming evidence in support of the use of smaller, non-cutting needles for diagnostic lumbar punctures, the use of larger cutting needles is still widespread in neurological departments [3,4,21]. In our outpatient clinic, where a cutting 22 G needle had previously been the needle of choice, we performed a prospective, interventional study, in order to test the feasibility, drawbacks, and potential benefits of changing the needle to a 25 G non-cutting needle.…”
Section: Discussionmentioning
confidence: 98%
“…Although proven to reduce the occurrence of PDPH, the usage of small, non-cutting needles is still not widespread in neurology departments [2]. In a UK survey, a cutting needle was used in over 70% of neurology units, and only two of 48 units reported using a gauge smaller than 22 G [3]. In a US survey, the use of non-cutting needles was even lower, as only 2% of the responding neurologists reported that they routinely used this type of needle [4].…”
Section: Introductionmentioning
confidence: 99%
“…A 1996 survey of senior registrars in all departments of neurology and neurosurgery in the United Kingdom found that 15% of respondents reported using atraumatic needles and that 73% recommended bed rest for up to 6 hours after completion of the LP. 70 A similar survey of 2287 practicing neurologists in the United States found that 2% used atraumatic needles. 70 Neurologists did not use atraumatic needles due to lack of knowledge of them or because the needles were not available for use in their institution.…”
Section: How Should This Procedures Be Taught or Learned?mentioning
confidence: 99%
“…70 A similar survey of 2287 practicing neurologists in the United States found that 2% used atraumatic needles. 70 Neurologists did not use atraumatic needles due to lack of knowledge of them or because the needles were not available for use in their institution. 71 The American Board of Internal Medicine recommends 3 to 5 LPs as a minimum standard for ensuring competence in completing LPs.…”
Section: How Should This Procedures Be Taught or Learned?mentioning
confidence: 99%
“…[ 7 A 1996 survey of UK neurological departments found that only 8% would consider the EBP before 72 hrs had passed after lumbar puncture. 34 Safa-Tisseront et al, 35 in a prospective, uncontrolled, observational study, found a delay of less than 4 days from dural puncture before performing an EBP to be an independent risk factor for failure of the procedure. Yet, Safa-Tisseront et al were careful to state that failure of the EBP may be primarily related to the severity of the CSF leak and that their study should not be grounds for delaying the EBP.…”
Section: Conduct Of the Ebpmentioning
confidence: 98%